2018
DOI: 10.1186/s12877-018-0916-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-month home-based physiotherapy on duration of living at home and functional capacity among older persons with signs of frailty or with a recent hip fracture - protocol of a randomized controlled trial (HIPFRA study)

Abstract: BackgroundHealth concerns, such as frailty and osteoporotic fractures decrease functional capacity and increase use of health and social care services in the aging population. The ability to continue living at home is dependent on functional capacity, which can be enhanced by rehabilitation.We study the effects of a 12-month home-based physiotherapy program with 12-month follow-up on duration of living at home, functional capacity, and the use of social and health care services among older persons with signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 64 publications
0
21
0
2
Order By: Relevance
“…Furthermore, European and North American studies have also shown that care provision by more nurses with at least bachelor's degrees are associated with lower mortality after surgery [37,38]. Physical therapy also important to enhance functional capacity and postpone the need for institutional care, and diminish the use of social and health care services for the older with signs of frailty or with a recent hip fracture [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, European and North American studies have also shown that care provision by more nurses with at least bachelor's degrees are associated with lower mortality after surgery [37,38]. Physical therapy also important to enhance functional capacity and postpone the need for institutional care, and diminish the use of social and health care services for the older with signs of frailty or with a recent hip fracture [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our frailty group is part of the HIPFRA study [16], which is a randomized controlled trial carried out to investigate the effects of 12-month supervised physical exercise intervention on the days lived at home in a 24-month period (the primary outcome). Secondary outcomes are physical functioning, health-related quality-of-life (HRQoL), severity of frailty, and use of social and health-care services.…”
Section: Designmentioning
confidence: 99%
“…Participation was voluntary and persons interested received comprehensive oral and written information about the study. For a more detailed description see [16].…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations